Assessment the role of performing temporary ileostomy in rectal cancer surgery - جبيلي سهير; أكثم قنجراوي; علي علوش (Latakia University Journal -Medical Sciences Series, 2023)
Background: Anastomotic leakage is considered a potentially severe complication after colorectal surgery with increasing morbidity and mortality, and whether outcome is modulated by temporary ileostomy, which have been shown to decrease anastomotic leakage and improve final outcome, is unclear. Aim: The purpose of this study was to determine the frequency of anastomotic leakage after surgery and the effect of performing ileostomy on the incidence. Materials and Methods: This was a prospective comparative study involved 41 patients with a diagnosis of rectal cancer who underwent low anterior rectal resection at Department of General Surgery, Tishreen University Hospital, Lattakia, during the period between 2022-2023. Patients were divided into two groups: group 1 (19 patients) included patients who underwent ileostomy, and group 2 included patients who didn’t undergo protective ileostomy (22 patients). Results: Out of 41 patients, 29 patients were male (70.7%) and 12 patients were female (29.3%), with mean age of the patients was 62.5±7.3 year. Majority of the rectal cancer patients were found in stage III (68.3%) with presence a history of radiotherapy in 65.9% of the patients before surgery. Stapled technique was used for anastomosis in 33 cases (80.5%) with performing protective ileostomy in 19 cases (46.5%). The rate of anastomotic leakage was lower in patients with temporary ileostomy (5.3% versus 13.6%) with presence of significant difference, p:0.04. In addition to, the rate of anastomotic leakage was significantly higher with increasing age (65.20±4.2 versus 59.7±5.4, p:0.001) and in the case of handsewn colorectal anastomoses (25% versus 6.1%, p:0.02). Conclusion: The current study demonstrated presence of favorable results and lower frequency of anastomotic leakage in patients who underwent low anterior rectal resection in presence of temporary ileostomy.